Հակոբ երեց Ամասիացի (Էմասիացի). հայկական ուշ միջնադարի նորահայտ բանաստեղծը - Առաքելյան, Անի (Մատենադարան)
The songbook (“Davtar,” Ms M3751) of Gevorg Akhverdyan who collected samples of folklore, has preserved six taghs (poems) written by a late medieval Armenian poet, priest Yakob Amasiats‘i. There is almost no information about this poet in the Armenian manuscript catalogues and other printed sources, and his poems have survived only in this single manuscript. A study of the Manuscripts W160 and W514 allows to conclude that priest Yakob Amasiats‘i (Emasiats‘i) mentioned in them is the same person as the author of the poems in Ms M3751, since they display a number of common features: the specific language which took shape in the 17th century (classical Grabar with elements of the spoken language) and some lyrical motives – conversation with oneself, reflection of one’s state of mind, examination of his own self and the world, personal experience and feelings. If, nonetheless, new facts emerge in the future, witnessing that these Yakobs are two different authors, one may assess the mentioned commonalities as an evidence of a specific late medieval poetic thinking characteristic of the poets of the province Amasia of Lesser Armenia. В Песеннике («Давтар», рук. М 3751) Геворга Ахвердяна, собиравшего образцы устного творчества, сохранилось шесть неизвестных стихотворений позднесредневекового армянского поэта Акоба иерея Амасийского (Емасийского). В каталогах рукописей и печатных источниках сведения о нем почти отсутствуют, а стихи сохранились только в указанной рукописи. Однако изу- чение венских рукописей №160 и №514 позволяет предположить, что упомянутый в них Акоб Амасийский – это то же лицо, что и автор стихов в М 3751, поскольку между ними много общего: сформировавшийся в 17-ом веке литературный язык (классический грабар с элементами живого языка), лирические мотивы – беседа с самым собой, отражение душевного состояния человека, вглядывающегося в собственное “Я” и мир жизненных обстоятельств и личных переживаний. Если, тем не менее, обнаружится, что Акобов следует считать двумя разными авторами, упомянутые общие черты можно будет расценивать как свидетельство об особом поэтическом мышлении позднего средневековья, свойственном стихотворцам области Амасия в Малой Армении.
Keywords: Հրապարակումներ; Հայ գրողների կյանքն ու գործունեությունը